2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.260048
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Skin-Electrode Impedance Using Concentric Ring Electrode

Abstract: A significant contributor to artefact generation in surface electromyography (sEMG) and, functional electrical stimulation (FES) intensity is the skin-to-electrode impedance (Z(S/E)). While using electrolytic gels may initially lower Z(S/E), the impedance may not remain stable. It can vary over time due to changes in underlying structures such as sweat glands and physical deformations due to movements. An experiment seeking to identify major factors in the reduction of Z(S/E), and therefore mitigate these arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The value of Z ES is represented by a series of three impedances consisting of electrode metal impedance, gel impedance, and skin layer impedances which include epidermis and subdermal impedances. According to Besio et al [56], in the suitable contact between electrode and skin surface, the amount of Z ES is less than 10 kΩ. To achieve the value of Z ES in this study, port 1 of Mini VNA Pro is directly connected to the on-body transmitter electrodes via the connecting cable.…”
Section: Circuit Model Simulationmentioning
confidence: 99%
“…The value of Z ES is represented by a series of three impedances consisting of electrode metal impedance, gel impedance, and skin layer impedances which include epidermis and subdermal impedances. According to Besio et al [56], in the suitable contact between electrode and skin surface, the amount of Z ES is less than 10 kΩ. To achieve the value of Z ES in this study, port 1 of Mini VNA Pro is directly connected to the on-body transmitter electrodes via the connecting cable.…”
Section: Circuit Model Simulationmentioning
confidence: 99%
“…EMG is an inherently random, nonstationary and nonlinear signal that is susceptible to interference from socket movement and sweat-related skin impedance changes (Besio and Prasad 2006;Alemu et al 2003). It is also difficult when using surface EMG to discriminate the activity of deep muscles from that of more superficial ones (De Luca 2002), limiting the potential for multi-DOF control.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate electrode adhesion to the skin is important for maintaining EMG signal quality and sensory threshold to electrical stimulation. Skin abrasion, electrolytic gel interfaces and pressure on the electrode surface have been recommended to reduce impedance and hold the electrode in place [30]. This study showed that impedance and sensory threshold was higher at the posterior area compared to the anterior and middle areas.…”
Section: Influence Of Impedancementioning
confidence: 58%
“…The electrode-skin impedance is one of the main elements of artefact in surface EMG recording and electrical stimulation intensity [30,31]. The skin at the temple over the AT muscle was divided into nine sites which were a 3x3 grid in this study.…”
Section: Influence Of Impedancementioning
confidence: 99%